Watershed associations in West Virginia: their impact on environmental protection - Cline, Sarah A.; Collins, Alan R. (Elsevier, 2003)
Grassroots watershed associations have formed as an avenue to facilitate public involvement in protecting watersheds. Growth in the number of watershed associations has created a need to evaluate whether their existence enhances environmental protection by local communities. In this research, environmental protection was measured by the number of watershed protection activities conducted and amount of funding directed towards protecting surface waters by non-profit, volunteer organizations. Regression models were utilized to examine the influence of population demographic and watershed characteristics variables to explain the formation of watershed associations along with watershed protection activities and funding. Regression results showed that the presence of watershed associations had positive impacts on both the number of activities and financial resources acquired. The results confirm that watershed associations enhance the ability of communities to obtain funding and to implement watershed protection actions. Thus, watershed associations serve as an effective institution for promoting environmental protection. -- Online Abstract